Pengaruh Keragaman Produk Lokasi Dan Kualitas Layanan Terhadap Keputusan Pembelian Pada Toko Viktory Kalabahi Kabupaten Alor - Anigomang, Ferdinand Romelus (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to determine the effect of product diversity, location and service quality on purchasing decisions at the Victory Kalabahi store in Alor Regency. This type of research is associative with a qualitative approach. The data used in this study are primary data obtained through the distribution of questionnaires to all consumers who shop at Victory Mart during the study period. The population in this study were all consumers who came to shop at the Victory Kalabahi store in Alor Regency. The sampling technique used in this study was accidental sampling. The accidental sampling method is a sampling technique based on coincidence, namely anyone who happens to meet the researcher at the location during the study period and is considered suitable to be a respondent. The statistical method used in this study is multiple linear regression by looking at the significant value of the t test and the significant value of the F test as a benchmark in testing the hypothesis and the results of data processing using the assistance of the IBM SPSS 22 For Windows program. The results of the study prove that: 1). Product diversity has a partial effect on purchasing decisions as evidenced by a significance value of 0.000% <0.05%, so that the results of this study accept H1. 2). Location has a partial effect on purchasing decisions as evidenced by a significance value of 0.001% <0.05%, so the results of this study accept H2. 3). Service quality has a partial effect on purchasing decisions as evidenced by a significance value of 0.005 <0.05%, so the results of this study accept H3. 4). Product diversity, location and service quality have a simultaneous effect on purchasing decisions as evidenced by a significance value of 0.000 <0.05%, so the results of this study accept H4.